2010
DOI: 10.1386/macp.6.1.45/1
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities of Web 2.0: Potentials of learning

Abstract: Starting with the empirical evidence regarding young people's attitudes towards the Internet with focus on the social web in the every day lives of adolescents, the article discusses what successful learning can be like. Furthermore, an Austrian pilot study on learning with Web 2.0 encompassing nine schools is outlined. In this project children worked together on a school-embracing wiki on Austrian national parks. Through the evaluation of the project, which included questionnaires, interviews and focus group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Research carried out by [12] reported a pilot study to evaluate the Wiki collaborative tool and investigate whether this could be used as a learning tool in schools. The results suggested that the use of this tool can enhance learning and encourage collaborative learning skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research carried out by [12] reported a pilot study to evaluate the Wiki collaborative tool and investigate whether this could be used as a learning tool in schools. The results suggested that the use of this tool can enhance learning and encourage collaborative learning skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Paus-Hasebrink et al in a study [15] on learning with Web 2.0 involving students from nine schools worked together on a school-embracing wiki on Austrian national parks found that wikis help youngsters to learn about ownership and authorship, and to understand issues of control and credit within the intellectual world. This study also revealed that students gained experience in both researching and selecting information, as well as in evaluating it.…”
Section: E-learning Opportunities With Web 20mentioning
confidence: 99%
“…Web 2.0 tools for video integration help in classrooms projects, presentations, parent meetings, etc. Modern teaching pedagogy promoting project-based learning by encouraging collaboration and participation among students has been made possible by Web 2.0 tools [21]. They are selfdirected, provide personalized learning environments within collaborative learning contexts [22], allow users to create and manage their own content, and facilitate discussion in an interactive manner.…”
Section: Emerging Developments In Webmentioning
confidence: 99%